LACC1 regulates changes in the intestinal flora in a mouse model of inflammatory bowel disease - Zheng-Yuan Xu; Jin-Chun Wang (BMC Gastroenterology, 2023)
Abstract Background The aim of this study was to explore the mechanism whereby LACC1 regulates the intestinal flora in a mouse model of inflammatory bowel disease (IBD). Methods C57BL/6 and Lacc1 −/− mice were used to establish a mouse model of IBD induced by dextran sodium sulfate (DSS). The effects of Lacc1 deletion in mice were evaluated. Changes in the body weight and stool blood were recorded daily. After 7 days of successful modeling, the mice were sacrificed, blood was collected from the eyeballs, the entire colon was dissected and separated, and the length of the colon was measured. Results Compared with the wild-type (WT) DSS model group, the Lacc1 −/− DSS model group showed a significantly higher disease activity index score (P < 0.05), significantly faster weight loss (P < 0.05), and a significantly shorter colon (P < 0.05), indicating that the colonic mucosal tissue was seriously damaged in the Lacc1 −/− DSS model group (P < 0.05). Serum IL-1β, IL-6, TNF-α, and IFN-γ levels were significantly higher in the Lacc1 −/− DSS model group than the WT DSS model group. Principal coordinate analysis showed that there were significant microbiome differences between the WT, Lacc1 −/− , WT DSS model, and Lacc1 −/− DSS model groups (P < 0.05). Linear discriminant analysis effect size analysis showed that under natural conditions, Lacc1 −/− mice had significant changes in their intestinal flora compared with control mice (LDA value > 3 or < 3, P < 0.05). Conclusions Lacc1 deletion aggravates DSS-induced IBD in mice.